DECODING THE THERAPEUTIC POTENTIAL OF EMPON-EMPON: A BIOINFORMATICS EXPEDITION UNRAVELING MECHANISMS AGAINST COVID-19 AND ATHEROSCLEROSIS - HASANAH, NUR; SAPUTRI, FADLINA CHANY; BUSTAMAM, ALHADI; SANGHIRAN LEE, VANNAJAN; YANUAR, ARRY (International Journal of Applied Pharmaceutics, 2024)
Objective: This study aims to elucidate the main compounds and mechanisms of action of Empon-empon (EE), a traditional Indonesian herb used for treating COVID-19 and atherosclerosis, utilizing an integrated network pharmacology and molecular docking approach. Methods: Active compounds in EE were obtained through the KNApSAcK, screening active compounds using parameters: oral bioavailability (OB) ≥ 30% and drug-likeness (DL) ≥ 0.18. Compound-related target genes were collected from GeneCard, ChemBL, and Traditional Chinese Medicine Systems Pharmacology (TCMSP). Disease targets were obtained from the GeneCard database. The protein-protein interaction (PPI) network was built using STRING and visualized using Cytoscape. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis using ShinyGO. Molecular docking analysis using Autodock Vina in PyRx. Results: We identified 18 main compounds in EE. PPI analysis obtained 5 central EE targets involved in treating COVID-19 and atherosclerosis, namely E1A Binding Protein P300 (EP300), Heat Shock Protein 90 Alpha Family Class A Member 1 (HSP90AA1), SRC Proto-Oncogene (SRC), Estrogen Receptor 1 (ESR1), and RELA Proto-Oncogene (RELA). GO and KEGG analysis illustrated EE's pharmacological effects through pathways in cancer, lipid and atherosclerosis, and PI3K-Akt signaling, including Coronavirus disease. Catechin and quercetin exhibited the strongest binding affinity to EP300; licarin B and delphinidin to HSP90AA1; epicatechin and delphinidin to SRC; galangin and ellagic acid to ESR1; and guaiacin and licarin B to RELA. Conclusion: This research provides a strong foundation regarding the main compound and mechanism action of EE in treating atherosclerosis and COVID-19, suggesting potential as a novel therapeutic agent.